MEMBANGUN KINERJA MELALUI PENGEMBANGAN KOMITMEN GURU DI KOTA SEMARANG - -, Nurhayati (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2011)
This study aims to analyze the performance of Primary School teachers in the city of Semarang. This study uses the variables of organizational culture, job satisfaction, and commitment to analyze the influence of teacher performance. In addition, studies using this type of research that is in use is the "Explanatory Research" or the study is explained, that this study emphasizes the relationship between variables by testing the hypothesis of the study description contains descriptions but the focus is on the relationship between variable.menganalisis influence the level of commitment of teachers to schools. The population in this study were primary school teachers in the city of Semarang. this study is to use random sampling procedure that the sample selection process in which all members of the population has an equal opportunity to choose from. This sample amounted to 83. The results showed that the variables of organizational culture, job satisfaction have a significant positive effect on commitment. Variables of organizational culture, job satisfaction and commitment showed a significant positive impact on the performance of human resources.